Implementation of SAK ETAP in the Financial Reports of Village-Owned Enterprises (BUMDes) Makmur Anugerah Lestari Sukamakmur Village, Ciomas District, Bogor Regency - Yan Noviar, Abdul Kohar (Genius Journals, 2023)
This research was conducted to find out whether BUMDes Makmur Anugerah Lestari has implemented SAK ETAP in presenting its financial reports. The type of research carried out in this research is descriptive qualitative. The type of data used is qualitative data. Qualitative data is data obtained through analysis carried out by direct interviews to obtain data and answer problem formulations regarding the implementation of SAK ETAP in Village-Owned Enterprises. The data sources used are primary data and secondary data. Based on the results of research on the BUMDes Makmur Anugerah Lestari, it can be concluded as follows: BUMDes Makmur Anugerah Lestari has made financial reports on its business but has not made financial reports in accordance with SAK ETAP. In recording or bookkeeping all transactions from business activities, not all follow the correct accounting provisions such as journals, ledgers and other accounting provisions. BUMDes Makmur Anugerah Lestari has records in the form of a cash book which contains information on cash expenditure and income. BUMDes Makmur Anugerah Lestari in its recording and bookkeeping is still based on the management's understanding only. BUMDes Makmur Anugerah Lestari should prepare complete financial reports in accordance with SAK ETAP, so that financial position, profit/loss, changes in equity, smooth cash flow and notes on financial reports can be known. For this reason, BUMDes must choose managers who have an understanding in preparing financial reports.
Keywords: Sak; etap; bumdes